2009
DOI: 10.1089/bfm.2008.0114
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability in Preterm Infants by Feeding Type: Mother's Milk Versus Formula

Abstract: Background and Objective: Intestinal permeability in preterm infants represents a critical balance between absorption of nutritional agents and protection from dangerous pathogens. This study identified the relationship between feeding type (human milk and formula) and intestinal permeability as measured by lactulose to mannitol ratio in preterm infants in the first postnatal month. Study Design: Sixty-two preterm (Յ32 weeks of gestation) infants had assessment of feeding type and evaluation with enteral lactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 14 publications
4
100
2
2
Order By: Relevance
“…Since the intestinal barrier is underdeveloped in pre-term babies, the influence of breast milk is particularly important. A study on pre-term infants in the first month post-birth found that those predominately fed human milk demonstrated lower intestinal permeability when compared with those fed minimal or no human milk (Taylor et al, 2009). A similar effect of breast feeding on intestinal permeability has also been reported for full-term babies (Catassi et al, 1995).…”
Section: Role Of Breast Milk In Intestinal Barrier Maturationmentioning
confidence: 75%
“…Since the intestinal barrier is underdeveloped in pre-term babies, the influence of breast milk is particularly important. A study on pre-term infants in the first month post-birth found that those predominately fed human milk demonstrated lower intestinal permeability when compared with those fed minimal or no human milk (Taylor et al, 2009). A similar effect of breast feeding on intestinal permeability has also been reported for full-term babies (Catassi et al, 1995).…”
Section: Role Of Breast Milk In Intestinal Barrier Maturationmentioning
confidence: 75%
“…For example, it has been shown that intestinal permeability decreases faster in breast-fed newborns compared with formula-fed babies [24,25]. A study by Taylor et al investigating the effect of breast milk volume on intestinal permeability in preterm infants (≤ 32 weeks) showed that breast milk promotes intestinal closure earlier and in a more consistent manner than formula fed babies during the first post-natal month and that breast milk doses greater than 25% of total feeds appear to play a role in the low intestinal permeability at the end of the first post-natal month compared with the group of infants who received minimal or no breast milk [52]. In addition, there are also findings that indicate that enteral feeding induces an increase in intestinal barrier function [26].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have indicated that breast milk could decrease intestinal permeability [13][14][15]. A study on pre-term infants during the first month of life indicated that those predominantly breastfed have Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4 Ex vivo intestinal resistance in mouse colon (a) and ileum (b). Transepithelial resistance (Rte) in colon and ileum (a, b) is determined by amplitude of voltage deflection generated by short intermittent current pulses and the exposed tissue surface area Intestinal permeability is expressed as the mean of basolateral concentration of FD4 (lg/ml/cm 2 /min) lower intestinal permeability when compared to those fed with minimal or no breast milk [14].…”
Section: Discussionmentioning
confidence: 99%